Indefinite integral calculus - Manzanares, Ernesto M. (Palo, Leyte : ELEGMAR, 1995)
The primary aim of this book is to give the students the complete tools in integration. All types of integrations are discussed in a very logical way, thus, giving the students a very clear picture as to what formula they are going to use when a problem in integration arises.
1. Integration; fundamental integration formulas -- 2. Integration by substitution -- 3. Integration of rational fractions.
Includes indexes.
Keywords: CALCULUS; CALCULUS, INTEGRAL; MATHEMATICS -- INTEGRATION -- INTEGRAL